Hand-made Temporalities - Rennie, James Julian (BBDS - Black Book: Drawing and Sketching, 2024)
We all store photos from our past – often in shoe boxes tucked away up in the attic. I store my dad’s hand-drawn cards - addressed to me (and later to me and / or my partner). This paper proposes the idea that my dad’s personal card drawings (and associated texts) are a visual memory vault for me from various moments of my early life. Because the cards are almost always dated, they allow a type of memory time travel backwards into that exact temporality. The written text topics vary: my father may be thanking me for a phone call to my Mum; or thanking me for a gift to him; or notification of a death of some local person his town; or simply describing the weather of that weekend; or a fatherly rebuke to do something that I had forgotten to do! The rediscovery of these artifacts is a visual signpost to exactly what was happening at date in time. As we all know, this can happen in association with a particular scent or a certain song, our memories and emotions flood back to that special moment with a few moments of intense nostalgia. This paper will unpack some of my shoe boxes and present a few of my Father’s cards to the reader showing the humility and grace of his early morning hand-made doodles that have lain dormant for years. Will we do the same with the myriads of emails or text messages that bombarde our current uber-paced lives?